Children are safe in schools: a review of the Irish experience of reopening schools during the COVID-19 pandemic. (June 2021) - White, P.; Ceannt, R.; Kennedy, E.; O'Sullivan, M.B.; Ward, M.; Collins, A.
Abstract: Objectives: Schools in the Republic of Ireland reopened to students and staff in late August 2020. We sought to determine the test positivity rate of close contacts of cases of coronavirus disease 2019 (COVID-19) in schools during the first half-term of the 2020/2021 academic year. Methods: National-level data from the schools' testing pathway were interrogated to determine the positivity rate of close contacts of cases of COVID-19 in Irish primary, postprimary and special schools during the first half-term of 2020/2021 academic year. The positivity rates among adult and child close contacts were compared and the proportion of national cases of COVID-19 who were aged 4–18 years during the observation period was calculated to assess whether this proportion increased after schools reopened. Results: Of all, 15, 533 adult and child close contacts were tested for COVID-19 through the schools' testing pathway during the first half-term of the 2020/2021 academic year. Three hundred and ninety-nine close contacts tested positive, indicating a positivity rate of 2.6% (95% confidence interval: 2.3–2.8%). The positivity rates of child and adult close contacts were similarly low (2.6% vs 2.7%, P = 0.7). The proportion of all national cases of COVID-19 who were aged 4–18 years did not increase during the first half-term of the 2020/2021 school year. Conclusions: The low positivity rate of close contacts of cases of COVID-19 in schools indicate that transmission of COVID-19 in Irish schools during the first half-term of the 2020/2021 academic year was low. These findings support policies to keep schools open during the pandemic.